Forecasts of transformation in legal regulation of artificial intelligence for cybersecurity in Ukraine’s defence sector - Semenenko, Oleh; Shynkaruk, Nataliia; Tolok, Polina; Ostrovskyi, Serhii; Davydov, Ihor (Revista Interdisciplinar de Ciência Aplicada, 2025)
The development of industrial automation tools and systems together with the widespread use of modern information technology leads to a trend of constant growth of the level of automation of the technological process, control and management systems of industrial enterprises. Such trends have led to dynamic changes in the human capital of the industrial sector. From the point of view of analysis of the degree and stage of automation of production on transformation of characteristics of human capital the article is relevant and solves an important scientific task of systematization of factors of influence on changes of human capital. The article is aimed at forecasting possible changes in human capital caused by the implementation of solutions proposed by the industrial revolution Industry 4.0, revealing positive and negative indicators leading to development or degradation, both human capital and industrial enterprise. The main methods used to solve the tasks and achieve goals are a systematic approach that allows you to take into account the complexity of human capital as a result of individual characteristics of an individual employee, both professional and personal, functional-system method was used to form the concept of industrial enterprises development with the active development of automation and ranking of automation stages depending on the applied technologies, as well as the structural and dynamic analysis of the transformation of the human capital to assess the trend of development of human capital during a certain period. Studies have shown that changes in working conditions in industrial enterprises, as a result of automation and introduction of innovative information technologies, have caused changes in the basic characteristics of human capital. The system approach in analysing the most important characteristic of human capital, which will allow to be successful in the modern realities of the labor market, has shown that changes in approach to education will reduce the shortage of highly qualified employees. It has been revealed that the transformation has influenced not only human capital, but also the forms and conditions of labor relations. Positive and negative changes in human capital caused by the new industrial revolution have been noted. The material of the article will be of interest to heads of enterprises, IT project managers.